The Design and Build a Web-Based Purchasing Information System using Agile Methods at Darma Store - Ikhwan Muhsinin, Yahya; Sudarmilah, Endah (Journal of Computer Networks, Architecture and High Performance Computing, 2025)
Increased electronic media can help business efficiency in customer service and sales. The implementation of Business to Customer (B2C) focuses on operational improvements which include developing more effective marketing strategies providing more responsive and personalized customer service which aims to improve customer experience and strengthen long-term business relationships. Software implementations are designed to improve operational processes, optimize workflows and minimize time required. This research aims to design and build a web-based online ordering and purchasing information system at the Darma Building Store. The method used in this research is software development. Agile Software Development uses agile methods which are very efficient and convincing in recognizing changes and higher customer satisfaction. The programming language used is Hypertext Preprocessor (PHP) with the Laravel framework. This research hopes that a web-based online ordering and purchasing information system can help the Darma Building Store manage inventory, increase operational efficiency, and making it easier for customers to make purchases. This system has several online ordering features, purchase reports and sales reports. This system is expected to help stores manage inventory, increase operational efficiency, and make it easier for customers to make purchases.